The Influence of Creative Personality and Goal Orientation on Innovation Performance - Zhou, Keqiucheng (Frontiers in Psychology, 2021)
The complexity and challenges of the external environment accelerate the awakening of the new generation of enterprise employees’ self-consciousness. Facing the continuous expansion of the information-based work mode, the traditional management mechanism of enterprises has a more limited impact on employee performance. Based on the goal-oriented theory, developing and excavating the creative personality traits of employees, making full use of goal-oriented behavior to improve their own innovation performance management path, are expected to become a new path to continuously enhance the innovation ability of enterprises. In this study, we take the employees of high-tech enterprises as samples to explore the influence mechanism of creative personality traits, goal orientation and employee innovation performance. The results show that goal orientation significantly moderates the relationship between creative personality traits and innovation performance. The mediating effects of learning goal orientation, performance certification orientation and performance avoidance orientation are all significant.